Enhancing Lecturer Performance through Management and Islamic Values in Higher Education - Ika Kartika; Hamidah; Hania Aminah; Antoni Ludfi Arifin (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Lecturer performance management is vital for improving the quality of higher education, particularly in Islamic universities. This study aims to analyze how performance management enhances lecturer quality, focusing on evaluation practices and professional development aligned with teaching, research, and community service. A qualitative approach was used, employing library research and content analysis to examine books, journal articles, and regulations from 2018 to 2024. The analysis included institutional documents, such as evaluation guidelines, to provide context-specific insights. The findings show that periodic evaluations provide constructive feedback, boost motivation, and identify strengths and weaknesses, encouraging continuous improvement through training, collaborative research, and teaching innovation. The integration of Islamic values, such as ethical conduct and religious outreach, enriches the evaluation process, aligning with the institution’s mission. Performance management contributes to better teaching quality, increased research output, and stronger community engagement, enhancing institutional competitiveness. However, reliance on literature limits empirical insights. This study concludes that systematic performance management, incorporating academic and Islamic principles, is a key strategy for developing lecturer professionalism and strengthening the identity of Islamic universities.